2018
DOI: 10.15406/oajs.2018.02.00085
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human resource outsourcing with regards to competitiveness of organizations

Abstract: Human resource outsourcing means that personnel-related matters are contracted to another organization. In other words, this refers to the transfer of responsibility for the management and application of human resource processes to an external party. The war for talent in the ever changing business environment is an essential factor that contributes to the outsourcing arrangement. The dynamic and complex nature of legal environment may also lead companies to engage with external contractors in order to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Essas dificuldades impostas à gestão tem reflexo na capacidade de aperfeiçoamento do desempenho humano da Unidade. Sem um processo que julgue ou estime o valor, a excelência e as competências de uma pessoa, assim como a sua contribuição para o negócio, restará comprometida a sua competitividade e cumprimento dos objetivos organizacionais (Bhushan, Gujarathi, Kaur, & Arumugam, 2018). Para Chiavenato (2020) a palavra monitorar tem o significado de seguir, acompanhar, orientar e manter o comportamento.…”
Section: Contexto Jurídico E Gestão De Pessoasunclassified
“…Essas dificuldades impostas à gestão tem reflexo na capacidade de aperfeiçoamento do desempenho humano da Unidade. Sem um processo que julgue ou estime o valor, a excelência e as competências de uma pessoa, assim como a sua contribuição para o negócio, restará comprometida a sua competitividade e cumprimento dos objetivos organizacionais (Bhushan, Gujarathi, Kaur, & Arumugam, 2018). Para Chiavenato (2020) a palavra monitorar tem o significado de seguir, acompanhar, orientar e manter o comportamento.…”
Section: Contexto Jurídico E Gestão De Pessoasunclassified
“…Furthermore, in education field, the effort to improve the quality of education and achieve quality human resources in accordance with national competency standards, it is necessary to implement a system of assessing learning outcomes that are good and planned (Sujarwo;Sukmawati;Yahrif, 2019) and to contextualize those professional competencies (Ma et al, 2018). There are some previous research results such as showed statistically significant differences between education contribution and competencies (Akatay et al, 2015;Bahar & Köroğlu, 2020;Kunskaja, 2019;Masri & Jaaron, 2017;Melliana et al, 2018;Seetharaman A, 2018).…”
Section: Introductionmentioning
confidence: 99%